Synthesis of isohexide-di(ether-ene)s and ADMET polymerization - Rajput, Bhausaheb S.; Lekshmy, Kalpakasseril Girija; Menon, Shamal K.; Chikkali, Samir H. (Green Materials, 2017)
As the fossil fuel reserves deplete and the greenhouse gases increase, the scientific community is challenged to provide sustainable solutions. Sugar-based isohexides can be modified to prepare a library of isohexide-diene monomers for polymerization. Such isohexide diene monomers can be subjected to Acyclic Diene Metathesis Polymerization to obtain green materials. Here we report a single step synthetic protocol to access a small family of isohexide-di(ether-ene)s and the corresponding polymers. The isohexide di(ether-ene)s 2a-2c could be isolated in good to excellent yields under optimized conditions. The resultant isohexide-di(ether-ene)s 2a-2c are potential versatile building blocks for pharmaceuticals and material science. The synthetic utility of 2a-2c was demonstrated by subjecting them to ADMET polymerization using Grubbs 1st and 2nd generation catalysts. The resultant viscous material was evaluated using 1H NMR and MALDI-ToF-MS, which suggests the formation of anticipated ADMET polymers